Memperdalam Kemampuan Berhitung Pada Anak Panti Asuhan Cinta Kasih - suhairani lusri lubis; Hairani Siregar (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Family, especially parents, are the first source of education every child have. The growth and development process of children are strongly determined by the role of the parents. Unfortunately, not all children have this opportunity. Orphanage home become the option for the unfortunate children to gain the same chance. However, the number of the children is not proportional to the number of orphanage educators. This, in turn, making the educators could not look after the children thoroughly which leads to another problem. The lack of guidance and supervision from the orphanage’s eductor in the children’s learning process results in decreased motivation and the desire to learn, further dimming their passion to achieve their dreams. The target is to increase their knowledge and their enthusiasm to learn so that they have motivations to reach their dreams. In this case work activity, one of the orphanage children is invited to learn various subjects via interesting study method by using youtube and mathematic applications such as Math Online and Sumas. The intervention method used in this activity is Zastrow’s casework method, which consist of intake and contract, assessment, planning, intervention, and evaluation. In addition, the tools used in the assessment step is Tools Assessment Ecomap.